Analisis Dinasti Fathimiyah di Mesir : Pertumbuhan, Perkembangan, dan Kemajuan - Rosidah Rosidah; Ratnasari Ratnasari; Yunan Fahri Ramadhan; Raditya Pangestu; Ahmad Maftuh Sujana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article explores the political, religious, and socio-cultural dimensions of the Fatimid Dynasty's rule in Egypt, highlighting its unique contributions to Islamic civilization. The Fatimid Caliphate, which ruled from 969 to 1171 AD, represented a significant Shi'a Islamic power that challenged the dominance of the Sunni Abbasid Caliphate. The study analyzes the origins of the Fatimid dynasty, its establishment in North Africa, and its eventual relocation of the capital to Cairo, which became a vibrant center of learning and governance. Special attention is given to the administrative reforms, religious tolerance policies, and architectural advancements initiated by Fatimid rulers. Additionally, the article examines the tensions and conflicts both internally and externally that eventually led to the dynasty’s decline. By using historical and historiographical methods, this research aims to provide a comprehensive understanding of how the Fatimid Dynasty shaped the political and religious landscape of medieval Egypt and left a lasting legacy that can still be seen in Egyptian culture and architecture today.